The PIN-FORMED Auxin Efflux Carriers in Plants - Zhou, Jing-Jing; Luo, Jie (International journal of molecular sciences, 2018)
Auxin plays crucial roles in multiple developmental processes, such as embryogenesis, organogenesis, cell determination and division, as well as tropic responses. These processes are finely coordinated by the auxin, which requires the polar distribution of auxin within tissues and cells. The intercellular directionality of auxin flow is closely related to the asymmetric subcellular location of PIN-FORMED (PIN) auxin efflux transporters. All PIN proteins have a conserved structure with a central hydrophilic loop domain, which harbors several phosphosites targeted by a set of protein kinases. The activities of PIN proteins are finely regulated by diverse endogenous and exogenous stimuli at multiple layers—including transcriptional and epigenetic levels, post-transcriptional modifications, subcellular trafficking, as well as PINs’ recycling and turnover—to facilitate the developmental processes in an auxin gradient-dependent manner. Here, the recent advances in the structure, evolution, regulation and functions of PIN proteins in plants will be discussed. The information provided by this review will shed new light on the asymmetric auxin-distribution-dependent development processes mediated by PIN transporters in plants.